2024
DOI: 10.1038/s41467-024-44704-6
|View full text |Cite
|
Sign up to set email alerts
|

Microglia govern the extinction of acute stress-induced anxiety-like behaviors in male mice

Danyang Chen,
Qianqian Lou,
Xiang-Jie Song
et al.

Abstract: Anxiety-associated symptoms following acute stress usually become extinct gradually within a period of time. However, the mechanisms underlying how individuals cope with stress to achieve the extinction of anxiety are not clear. Here we show that acute restraint stress causes an increase in the activity of GABAergic neurons in the CeA (GABACeA) in male mice, resulting in anxiety-like behaviors within 12 hours; meanwhile, elevated GABACeA neuronal CX3CL1 secretion via MST4 (mammalian sterile-20-like kinase 4)-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Some researchers have found through immunofluorescence experiments that the number of microglia increases and is activated when anxiety is generated. 8 Numerous articles have documented the close interaction between microglia and astrocytes. 62 Specifically, it has been observed that an increase in M1 microglia leads to the production of pro-inflammatory factors by astrocytes, whereas an increase in M2 microglia prompts astrocytes to produce anti-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have found through immunofluorescence experiments that the number of microglia increases and is activated when anxiety is generated. 8 Numerous articles have documented the close interaction between microglia and astrocytes. 62 Specifically, it has been observed that an increase in M1 microglia leads to the production of pro-inflammatory factors by astrocytes, whereas an increase in M2 microglia prompts astrocytes to produce anti-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…7 In 2024, a new study found that microglia drive a negative feedback to inhibit GABACeA neuronal activity, thus facilitating maintenance of brain homeostasis in response to acute stress. 8 And other studies have found that abnormal cortical excitability, atypical excitatory neurotransmission and increased levels of metabolites are significantly associated with anxiety and depression. 9,10…”
Section: Introductionmentioning
confidence: 96%
“…The occurrence of post-traumatic stress disorder (PTSD) following a single traumatic event highlights the potent influence of stress in the etiology of clinically relevant anxiety ( Yehuda et al, 2015 ). Acute stress exposure in mice is sufficient to induce anxiety symptomatology via several modalities, including restraint ( Kemp et al, 2022 ; Liu et al, 2023 ; Chen et al, 2024 ) and inescapable shock ( Tillage et al, 2020 , 2021 ; McGovern et al, 2022 ). The effect of acute stress also translates to humans ( Grillon et al, 2007 ; Daviu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%